2021
DOI: 10.7759/cureus.18224
|View full text |Cite
|
Sign up to set email alerts
|

Primary Combined Hepatocellular-Cholangiocarcinoma: A Case of Underdiagnosed Primary Liver Cancer

Abstract: Combined hepatocellular-cholangiocarcinoma (CHC) is a rare primary tumor of the liver. Histologically, it comprises components of both hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC) but is associated with a worse prognosis. International guidelines regarding its management are scarce, with surgical management (major hepatectomy) being the treatment of choice. In this report, we present a challenging case of a 73-year-old male with primary CHC who was not a surgical candidate but underwent hepatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The clinical appearance of cHCC-CCA is analogous to that of HCC and iCCA. In fact, it has usually nonspecific symptoms characterized by fatigue, abdominal pain, weight loss, pruritus, and, in advanced states, jaundice, ascites, acute cholangitis, and hepatomegaly [46]. Additionally, in cHCC-CCA patients, it is possible to find several tumour markers, such as alpha-fetoprotein, carcinoembryonic antigen, and carbohydrate antigen 19.9 [47][48][49].…”
Section: Epidemiology Clinical Features and Risks Factorsmentioning
confidence: 99%
“…The clinical appearance of cHCC-CCA is analogous to that of HCC and iCCA. In fact, it has usually nonspecific symptoms characterized by fatigue, abdominal pain, weight loss, pruritus, and, in advanced states, jaundice, ascites, acute cholangitis, and hepatomegaly [46]. Additionally, in cHCC-CCA patients, it is possible to find several tumour markers, such as alpha-fetoprotein, carcinoembryonic antigen, and carbohydrate antigen 19.9 [47][48][49].…”
Section: Epidemiology Clinical Features and Risks Factorsmentioning
confidence: 99%
“…But in this case, there is no significant rise in serum IgG4, which is then demonstrated in infrequent patients. Ayas et al, in one of the cases, observed that cholangiocarcinoma is a rare tumor with a poor prognosis and complex treatment, making it an undiagnosed entity [ 11 ]. But, in this case, the issue was identified as soon as he presented with the disease in the hospital, which led to better chances of responding to the provided treatment.…”
Section: Discussionmentioning
confidence: 99%